2015
DOI: 10.1155/2015/898790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug Resistance amongSalmonella entericaSerovar Typhimurium Isolated from Pig Faeces in Ashanti Region, Ghana

Abstract: Introduction. Salmonella typhimurium is associated with outbreaks of food-borne nontyphoidal salmonellosis (NTS) worldwide with marked multidrug resistance. Objectives. This study aimed to determine the prevalence of antibiotic resistant Salmonella typhimurium in pigs in Ashanti Region, Ghana. Methods. Faeces from 10 pigs per pig farm were collected and mixed to obtain 108 multiply-composite faecal samples. Standard microbiology and biochemical procedures were used to isolate and identify an S. typhimurium iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
(6 reference statements)
1
15
0
Order By: Relevance
“…This finding shows similar pattern of high resistant Salmonella spp in previous study in China, where the multidrug resistant (MDR) Salmonella spp reported to be 80% in food animals when tested against 17 commonly used antibiotics for clinical applications [33]. Previously, report from Ghana also reported high prevalence of Salmonella spp (66.7%) which where the MDR of the isolates were reported to be 52.8% [34]. Across the world, prevalence of Salmonella spp were reported in varying degree with very low prevalence in Europe (2%) than other continents which is in contrast with the current study [35].…”
Section: Discussionsupporting
confidence: 86%
“…This finding shows similar pattern of high resistant Salmonella spp in previous study in China, where the multidrug resistant (MDR) Salmonella spp reported to be 80% in food animals when tested against 17 commonly used antibiotics for clinical applications [33]. Previously, report from Ghana also reported high prevalence of Salmonella spp (66.7%) which where the MDR of the isolates were reported to be 52.8% [34]. Across the world, prevalence of Salmonella spp were reported in varying degree with very low prevalence in Europe (2%) than other continents which is in contrast with the current study [35].…”
Section: Discussionsupporting
confidence: 86%
“…In China, it is estimated that 97 000 metric tons of the approximately 210 000 metric tons of antibiotics produced yearly are used in animal husbandry. Thus, a rise in the number of resistant bacteria in the animal gut has been observed (Zhao et al ., ), compounded by the fact that more than half of administered antibiotics are not absorbed in the animal gut and are, therefore, shed in the faeces, exposing the environment to subtherapeutic levels of antibiotics and contributing further to AMR (Osei Sekyere and Adu, ; Zhao et al ., ).…”
Section: Amr In Veterinary and Agricultural Sourcesmentioning
confidence: 99%
“…Nonetheless, most of the reports on antibiotic use in food-animal production have been limited to the types of antibiotics employed, resistance of organisms isolated from these farms [24][25][26][27][28] and quantities of antibiotics used [25,26].…”
Section: Introductionmentioning
confidence: 99%